Peran Unit Zakat dalam Pemberdayaan Masyrakat: Studi Kasus di Desa Mojopuro, Jatiroto, Wonogiri - Nada Sofa Mariyah; Syauqi Syahla Ibtisamah; Fauzun Jamal (Lembaga Pengembangan Kinerja Dosen, 2025)
This research describes the role of the Zakat Collection Unit (UPZ) in community empowerment in Mojopuro Village, Jatiroto District, Wonogiri Regency. The background of this study lies in the condition of the UPZ, which had been established yet was not optimal in its management and functional capacity for zakat administration. Employing a qualitative approach with a case study method, data were collected through observations, interviews with BAZNAS and mosque administrators, as well as documentation of seminars and the inauguration of zakat administrators. The findings reveal that the establishment and inauguration of the UPZ by BAZNAS marked the beginning of strengthening village-level zakat institutions. Seminars for mosque administrators improved their understanding of zakat management in accordance with Islamic law and fostered collective awareness of the importance of zakat for economic empowerment. The UPZ plays a role in identifying mustahik, managing funds transparently, and distributing them through community-based productive programs. The UPZ, guided by BAZNAS, holds a strategic role in reinforcing the zakat management system at the village level and has the potential to become an effective instrument for community economic empowerment.